Reformasi Sistem Komunikasi Organisasi Pemerintah Indonesia dalam Meningkatkan Pelayanan Publik - Tumanggor, Timur; Kholil, Syukur (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This research aims to examine the reform of the Indonesian government's organizational communication system in improving the quality of public services. Based on data from various sources, it was found that the low community satisfaction index (73.42), the level of public participation which is still below the national target (58.7%), and the high number of complaints and cases of misuse of the village budget reflect the weak transparency and effectiveness of government communication. The research method used is a qualitative approach with case studies, through interviews, participatory observations, and document analysis. The results of the study show that there are seven main obstacles, including rigid bureaucracy, low communication literacy of apparatus, limited information technology, and lack of participatory strategies. Effective communication reform needs to be based on three main pillars: human resource capacity building, accountable digital technology integration, and opening up spaces for inclusive public participation. By building an adaptive, transparent, and collaborative communication system, public services can become more responsive and trusted by the public. This research makes a theoretical and practical contribution in shaping democratic governance and encouraging the transformation of bureaucratic culture towards a more open and socially just service system.